Workload and Work Discipline as Determinants of Employee Performance: Evidence from the Mining Industry - azwardi; Mohammad Eko Fitrianto; aryagustifram (Jurnal Ragam Pengabdian, 2026)
Employee performance is a critical factor in ensuring organizational sustainability, particularly in capital-intensive and high-risk industries such as mining. Increasing production targets without a proportional increase in workforce may intensify workload and undermine the effectiveness of work discipline, potentially undermining performance. This study aims to examine the effects of workload and work discipline on employee performance at PT Internasional Prima Coal. A quantitative approach with a causal Research design was employed. Data were collected through structured questionnaires distributed to all 78 employees using a census sampling technique. The collected data were analyzed using descriptive statistics, instrument testing, classical assumption tests, and multiple linear regression analysis. The results indicate that workload has a negative and significant effect on employee performance, suggesting that excessive physical and mental job demands reduce employees' ability to perform optimally. In contrast, work discipline shows a positive but insignificant effect on employee performance, indicating that disciplinary compliance alone is insufficient to enhance performance under high workload conditions. Simultaneously, workload and work discipline significantly Influence employee performance, although their overall contribution remains limited, implying that multiple organizational factors shape performance. This study concludes that effective workload management plays a more critical role than disciplinary enforcement in sustaining employee performance within high-demand mining environments. The findings provide practical insights for management to implement proportional workload allocation and integrate work discipline with supportive human resource management practices to achieve sustainable performance improvement